31P-NMR analysis of bio-oils obtained from the pyrolysis of biomass. Issue 6 (November 2010) - David, Kasi; Kosa, Matyas; Williams, Alex; Mayor, Rhett; Realff, Matthew; Muzzy, John; Ragauskas, Arthur
Background: The use of 2-chloro-4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaphospholane followed by 31 P-NMR analysis has been frequently employed to quantitatively characterize the structure of hydroxyl groups in lignin and, more recently, biodiesel. This technique serves as a valuable tool to determine aliphatic hydroxyls, phenolics and carboxylic acid groups in lignin and aliphatic hydroxyl groups in partially substituted glycerols.Results: This study demonstrates the application of this analytical technique to pyrolysis oils to allow efficient analysis and identification of important functional groups present in bio-oils and the measurement of moisture content.Conclusion: Phosphitylation followed by 31 P-NMR analysis was used to show that the moisture content of the loblolly pine bio-oil used in this study was 11.94%. The results also established that the bio-oils obtained from loblolly pine cellulose had higher levoglucosan content than the bio-oil obtained from the starting pine itself. In addition, the total phenolic content of bio-oil derived from loblolly pine milled wood lignin was greater than that obtained from the bio-oil from the loblolly pine cellulose. The data also highlighted the ability to track chemical transitions that take place during pyrolysis using 31 P-NMR.